Thermoplastic resin composition and method for producing the same, molded body as well as injection molded body and method for producing the same
The thermoplastic resin composition, with its specific monomer and polyurethane blend, addresses the low toughness and scratch issues of methacrylic resin compositions, achieving high transparency and resistance for outdoor use.
Patent Information
- Application Number
- JP2023159230
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-22
- Publication Date
- 2025-04-04
AI Technical Summary
Methacrylic resin compositions exhibit low toughness and are prone to scratches when used outdoors, limiting their application in molded bodies with mechanisms or exposed to environmental stress.
A thermoplastic resin composition comprising 50-99% methacrylic acid ester monomer units, 0.1-20% vinyl monomer units, 0.1-20% maleic acid and/or maleic anhydride monomer units, and 1-50% thermoplastic polyurethane with alicyclic rings, which enhances transparency, scratch resistance, and toughness.
The composition achieves high transmittance and low haze, providing excellent transparency, scratch resistance, and toughness, making it suitable for outdoor applications.
Smart Images

Figure 2025050434000001 
Figure 2025050434000002 
Figure 2025050434000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a thermoplastic resin composition and a method for producing the same, a molded article, and an injection molded article and a method for producing the same. [Background technology]
[0002] Methacrylic resins are characterized by having higher light transmittance, weather resistance, and rigidity as transparent resins than other plastic transparent resins, and have been used in a wide range of applications such as vehicle parts, lighting fixtures, building materials, signs, nameplates, paintings, and display device windows. Among them, methacrylic resin compositions are widely used as design parts for home appliances and office automation products and interior and exterior design parts for automobiles due to their excellent appearance. However, methacrylic resin compositions have the problem of low toughness and that the surface is scratched when used outdoors, and therefore their use is often restricted in molded articles with mechanical parts, applications where they are used in a distorted state, and outdoor use.
[0003] In Patent Document 1, a method of using a multi-layer (meth)acrylic rubber polymer is attempted to improve toughness. However, these compositions cause stress whitening. Stress whitening is haze that occurs when subjected to bending stress. Furthermore, scratch resistance has not been improved in these compositions, and remains a problem.
[0004] As another approach to improving toughness, Patent Document 2 considers compounding with elastomers and describes a transparent low-temperature impact-resistant plastic mixture consisting of a thermoplastic (TPU) and impact-improved poly(meth)acrylate. According to Patent Document 2, these plastic mixtures exhibit acceptable transparency as well as good impact resistance, high tensile modulus, and good weatherability. The plastic mixture uses a thermoplastic polyurethane having an aliphatic bond. Patent Document 2 shows that a transmittance of 83% is achieved with a mixture of impact-improved poly(meth)acrylate and impact-improved thermoplastic polyurethane having an aliphatic bond under the described test conditions, but a total light transmittance of 83% is insufficient for a transparent material. In addition, the transparency of a material is affected not only by the total light transmittance but also by the haze.
[0005] Patent Document 3 discloses a composition that uses an aliphatic isocyanate having a specific structure and exhibits high transmittance and low haze at the same time, particularly low haze and high transparency, in order to improve the insufficient transparency. However, the haze of the composition disclosed in Patent Document 3 is not sufficiently low, and there is room for improvement in order to use the composition as a transparent material. [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2003-183471 A [Patent Document 2] International Publication No. 2007 / 057242 [Patent Document 3] Special Publication No. 2015-532345 Summary of the Invention [Problem to be solved by the invention]
[0007] An object of the present invention is to provide a thermoplastic resin composition which exhibits high transmittance and simultaneously low haze, is excellent in transparency, scratch resistance and toughness. [Means for solving the problem]
[0008] That is, the present invention is as follows. [1] A thermoplastic resin composition comprising 50 to 99 mass% of a methacrylic resin (A) having a ring structure in its main chain, the methacrylic resin containing 80.0 to 99.9 mass% of methacrylic acid ester monomer units (a1), 0.1 to 20.0 mass% of vinyl monomer units (a2) copolymerizable with methacrylic acid ester monomers excluding methacrylic acid esters, maleic acid, and maleic anhydride, and 0 to 4.0 mass% of maleic acid and / or maleic anhydride monomer units (a3), and 1 to 50 mass% of a thermoplastic polyurethane (B) containing a structural unit (b1) derived from a polyester polyol and a structural unit (b2) derived from an isocyanate having an alicyclic ring. [2] The thermoplastic resin composition according to [1], wherein the structural unit (b2) derived from an isocyanate having an alicyclic ring has one alicyclic ring. [3] The thermoplastic resin composition according to [1] or [2], wherein the weight average molecular weight of the methacrylic resin (A) having a ring structure in its main chain, as measured by gel permeation column chromatography (GPC), is 50,000 to 250,000. [4] The thermoplastic resin composition according to any one of [1] to [3], wherein the amount of terminal unsaturated double bonds in the methacrylic resin (A) having a ring structure in the main chain is 0.01 mol % or less. [5] The thermoplastic resin composition according to any one of [1] to [4], wherein the vinyl monomer unit (a2) copolymerizable with the methacrylic acid ester monomer excluding the methacrylic acid ester, maleic acid, and maleic anhydride is an N-substituted maleimide monomer unit and / or a styrene-based monomer unit. [6] The thermoplastic resin composition according to [5], wherein the methacrylic resin (A) having a ring structure in the main chain contains 85 to 99.9 mass % of the methacrylic acid ester monomer unit (a1), 0.1 to 15 mass % of N-substituted maleimide monomer unit, and 0 to 10 mass % of styrene monomer unit. [7] The thermoplastic resin composition according to any one of [1] to [6], wherein a mass ratio of an isocyanate-derived structural unit having one alicyclic ring relative to a total mass of isocyanate-derived structural units contained in the thermoplastic polyurethane (B) is 70 mass% or more, relative to 100 mass%. [8] The method for producing the thermoplastic resin composition according to any one of [1] to [7], comprising a step of blending the methacrylic resin (A) having a ring structure in the main chain and the thermoplastic polyurethane (B) at a temperature in the range of 200 to 260°C. [9] A molded article comprising the thermoplastic resin composition according to any one of [1] to [7].
[10] An injection-molded article comprising the thermoplastic resin composition according to any one of [1] to [7].
[11] A method for producing an injection-molded article, comprising the step of molding the thermoplastic composition according to any one of [1] to [7] at a cylinder temperature of 200 to 260°C. Effect of the Invention
[0009] The thermoplastic resin composition of the present invention exhibits high transmittance and low haze at the same time, and is excellent in transparency, scratch resistance and toughness. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] [Thermoplastic resin composition] The thermoplastic resin composition of the present embodiment contains, relative to 100 mass% of the thermoplastic resin composition, 50 to 99 mass% of a methacrylic resin (A) having a ring structure in the main chain (hereinafter, sometimes abbreviated as "methacrylic resin (A)") and 1 to 50 mass% of a thermoplastic polyurethane (B). The methacrylic resin (A) contains 80.0 to 99.9 mass% of a methacrylic acid ester monomer unit (a1), 0.1 to 20.0 mass% of a vinyl monomer unit (a2) copolymerizable with a methacrylic acid ester monomer other than a methacrylic acid ester, maleic acid, and maleic anhydride (hereinafter, sometimes abbreviated as "vinyl monomer unit (a2)"), and 0 to 4.0 mass% of a maleic acid and / or maleic anhydride monomer unit (a3). The thermoplastic polyurethane (B) contains a structural unit (b1) derived from a polyester polyol and a structural unit (b2) derived from an isocyanate having an alicyclic ring. In this specification, unless otherwise specified, the total mass of all components of the thermoplastic resin composition is 100 mass %.
[0011] <Methacrylic resin (A) having a ring structure in the main chain> The methacrylic resin (A) having a ring structure in the main chain may contain at least one type of methacrylic resin, and one type of methacrylic resin may be used alone, or two or more types of methacrylic resins may be used in combination. The methacrylic resin (A) is required to contain, relative to 100 mass% of the methacrylic resin (A), 80.0 to 99.9 mass% of methacrylic acid ester monomer units (a1), 0.1 to 20.0 mass% of vinyl monomer units (a2) copolymerizable with methacrylic acid ester monomers excluding methacrylic acid ester, maleic acid, and maleic anhydride, and 0 to 4.0 mass% of maleic acid and / or maleic anhydride monomer units (a3).
[0012] <<Methacrylate ester monomer unit (a1)>> Examples of the methacrylic acid ester monomer that produces the methacrylic acid ester monomer unit (a1) contained in the methacrylic resin (A) include, but are not limited to, esters of methacrylic acid with an aliphatic alcohol which may be substituted, and esters of methacrylic acid with a hydroxyl group- and aromatic ring-containing compound. Examples of esters of methacrylic acid and optionally substituted aliphatic alcohols include, but are not limited to, methyl methacrylate, ethyl methacrylate, propyl methacrylate, isopropyl methacrylate, butyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate, t-butylcyclohexyl methacrylate, and 2,2,2-trifluoroethyl methacrylate. Examples of esters of methacrylic acid with a compound containing a hydroxyl group and an aromatic ring include, but are not limited to, phenyl methacrylate, benzyl methacrylate, and the like. Among these, from the viewpoints of availability and cost, methyl methacrylate and ethyl methacrylate are preferred as the methacrylic acid ester monomer unit (a1). The above methacrylic acid ester monomers may be used alone or in combination of two or more.
[0013] The content of the methacrylic acid ester monomer unit (a1) in the methacrylic resin (A) must be 80.0% by mass or more and 99.9% by mass or less, based on 100% by mass of the methacrylic resin (A). By making the content of the methacrylic acid ester monomer unit (a1) in the methacrylic resin (A) 99.9% by mass or less, decomposition of the resin during molding can be prevented, and the generation of the methacrylic acid ester monomer, which is a volatile component, and molding defects called silver can be effectively prevented. In addition, a further improvement in transparency can be expected when the resin is made into a thermoplastic resin composition. By making the content of the methacrylic acid ester monomer unit (a1) in the methacrylic resin (A) 80.0% by mass or more, the heat resistance generally required for molded products can be ensured. By having sufficient heat resistance, rigidity can also be ensured, and the strength generally required for molded products can be ensured.
[0014] The content of the methacrylic acid ester monomer unit (a1) is, from the viewpoint of obtaining a higher transmittance and at the same time a lower haze, and from the viewpoint of preventing yellowing of the thermoplastic resin composition, preferably 85.0 mass% or more, more preferably 90.0 mass% or more, and even more preferably 93.0 mass% or more, based on 100 mass% of the methacrylic resin (A).
[0015] <<Vinyl monomer unit (a2)>> Examples of "vinyl monomers copolymerizable with methacrylic acid ester monomers excluding methacrylic acid esters, maleic acid, and maleic anhydride" (hereinafter sometimes abbreviated as "copolymerizable vinyl monomers") that produce the vinyl monomer units (a2) contained in the methacrylic resin (A) include (meth)acrylic acid ester monomers and vinyl monomers other than (meth)acrylic acid ester monomers. Examples of (meth)acrylic acid ester monomers include, but are not limited to, acrylic acid ester monomers having one acrylate group and (meth)acrylic acid ester monomers having two or more (meth)acrylate groups.
[0016] Examples of acrylic acid ester monomers having one acrylate group include, but are not limited to, methyl acrylate, ethyl acrylate, n-propyl acrylate, n-butyl acrylate, sec-butyl acrylate, and 2-ethylhexyl acrylate.
[0017] Examples of the (meth)acrylic acid ester monomer having two or more (meth)acrylate groups include, but are not limited to, (meth)acrylic acid ester monomers in which both terminal hydroxyl groups of ethylene glycol or its oligomers are esterified with acrylic acid or methacrylic acid, such as ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, and tetraethylene glycol di(meth)acrylate; (meth)acrylic acid ester monomers in which hydroxyl groups of two alcohols, such as neopentyl glycol di(meth)acrylate and di(meth)acrylate, are esterified with acrylic acid or methacrylic acid; and (meth)acrylic acid ester monomers in which polyhydric alcohol derivatives, such as trimethylolpropane and pentaerythritol, are esterified with acrylic acid or methacrylic acid.
[0018] As the copolymerizable vinyl monomer that produces the vinyl monomer unit (a2), a (meth)acrylic acid ester monomer is preferred, and an acrylic acid ester monomer is more preferred. In particular, methyl acrylate, ethyl acrylate, and n-butyl acrylate are preferred, and further, methyl acrylate and ethyl acrylate are preferred because of their easy availability. The copolymerizable vinyl monomers which form the vinyl monomer units (a2) may be used alone or in combination of two or more kinds.
[0019] The content of the vinyl monomer unit (a2) is required to be 0.1% by mass or more and 20.0% by mass or less, relative to 100% by mass of the methacrylic resin (A), and is preferably 0.2% by mass or more, more preferably 0.5% by mass or more, preferably 15.0% by mass or less, and more preferably 7.0% by mass or less. From the viewpoint of obtaining a higher transmittance and at the same time a lower haze, it is particularly preferably 1.0% by mass or more, and particularly preferably 6.5% by mass or less.
[0020] In particular, when the vinyl monomer unit (a2) is a (meth)acrylic acid ester monomer unit (i.e., the copolymerizable vinyl monomer is a (meth)acrylic acid ester monomer), the content of the vinyl monomer unit (a2) in the methacrylic resin (A) is preferably within the above-mentioned range. By making the content of the vinyl monomer unit (a2) in the methacrylic resin (A) 0.1% by mass or more, it is possible to prevent degradation due to the decomposition of the methacrylic resin during molding, and the decomposition and yellowing of the thermoplastic polyurethane caused by radicals generated by the decomposition of the methacrylic resin, and it is possible to effectively prevent molding defects due to yellowing of the thermoplastic resin composition and generation of volatile components. In addition, by making the content of the vinyl monomer unit (a2) in the methacrylic resin (A) 20.0% by mass or less, it is possible to ensure the heat resistance generally required for molded products. In addition, the content of the vinyl monomer unit (a2) in the methacrylic resin (A) is preferably 0.4 mass% or less, particularly when a monomer having two (meth)acrylate groups is used, 0.25 mass% or less, when a monomer having three (meth)acrylate groups is used, and 0.15 mass% or less, when a monomer having four or more (meth)acrylate groups is used, relative to the methacrylic resin (A) (100 mass%), from the viewpoint of ensuring fluidity during injection molding and maintaining transparency.
[0021] In addition, examples of the "vinyl monomer other than (meth)acrylic acid ester monomer" that can be the "copolymerizable vinyl monomer" include, but are not limited to, α,β-unsaturated acids such as acrylic acid and methacrylic acid; unsaturated group-containing divalent carboxylic acids and their alkyl esters such as fumaric acid, itaconic acid, and cinnamic acid; styrene monomers such as styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, 3,4-dimethylstyrene, 3,5-dimethylstyrene, p-ethylstyrene, m-ethylstyrene, o-ethylstyrene, p-tert-butylstyrene, and isopropenylbenzene (α-methylstyrene); 1-vinylnaphthalene (α-methylstyrene); aromatic vinyl compounds such as olefin, 2-vinylnaphthalene, 1,1-diphenylethylene, isopropenyltoluene, isopropenylethylbenzene, isopropenylpropylbenzene, isopropenylbutylbenzene, isopropenylpentylbenzene, isopropenylhexylbenzene, and isopropenyloctylbenzene; vinyl cyanide compounds such as acrylonitrile and methacrylonitrile; unsaturated carboxylic acid anhydrides such as itaconic anhydride; maleimide, and N-substituted maleimides such as N-methylmaleimide, N-ethylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide; amides such as acrylamide and methacrylamide; and polyfunctional monomers such as divinylbenzene.
[0022] Among the above, it is preferable to use N-substituted maleimide monomers such as N-methylmaleimide, N-ethylmaleimide, N-phenylmaleimide, and N-cyclohexylmaleimide, which can introduce a ring structure into the main chain and exhibit high transparency and excellent heat deformation resistance when made into a thermoplastic resin composition, and styrene-based monomers which exhibit high transparency when made into a thermoplastic resin composition.
[0023] The content of the N-substituted maleimide monomer unit is preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more, based on 100% by mass of the methacrylic resin (A) having a ring structure in the main chain, from the viewpoint of exhibiting high transparency and excellent heat deformation resistance, and is preferably 15% by mass or less, more preferably 12% by mass or less, and even more preferably 10% by mass or less, from the viewpoint of improving the strength of the thermoplastic resin composition.
[0024] The content of the styrene monomer is preferably 0.1% by mass or more, more preferably 1% by mass or more, and even more preferably 2% by mass or more, based on 100% by mass of the methacrylic resin (A) having a ring structure in the main chain, from the viewpoint of exhibiting high transparency. Also, from the viewpoint of weather resistance of the thermoplastic resin composition and preventing generation of burnt resin during processing, the content is preferably 10% by mass or less, more preferably 8% by mass or less, and even more preferably 7% by mass or less.
[0025] <<Maleic acid and / or maleic anhydride monomer units (a3)>> The methacrylic resin (A) having a ring structure in the main chain may optionally contain maleic acid and / or maleic anhydride monomer units (a3). Maleic acid and maleic anhydride can be copolymerized with methacrylic acid ester monomers, but cannot be used in excess from the viewpoints of yellowing when made into a thermoplastic resin composition with thermoplastic polyurethane, preventing yellowing and silvering during molding and maintaining good weather resistance, so the content of maleic acid and / or maleic anhydride monomer units (a3) is preferably 0 to 4.0 mass% relative to 100 mass% of the methacrylic resin (A), more preferably 3.0 mass% or less, and even more preferably 2.0 mass% or less, and may not be contained.
[0026] <Method of introducing a ring structure into the main chain of a methacrylic resin> The methacrylic resin (A) contained in the thermoplastic resin composition of the present invention has a ring structure in the main chain. Methods for introducing a ring structure into the main chain skeleton of a methacrylic resin include a method of copolymerizing a maleic anhydride monomer or an N-substituted maleimide monomer with a methacrylic acid ester monomer, a method of copolymerizing a methacrylic acid ester with a monomer of the following formula 1, and then cyclizing the resulting mixture by heat treatment in the presence or absence of a catalyst to introduce a glutaric anhydride structural unit, as well as a method for introducing glutarimide and a method for introducing a lactone ring as described in JP-A-2021-015255. The introduction of an N-substituted maleimide skeleton into the main chain is preferred, as it reduces the acid value of the methacrylic resin composition, prevents the denaturation of the thermoplastic polyurethane, and does not use a substance that promotes the decomposition of the thermoplastic polyurethane when introducing a ring structure. In this case, in order to prevent the thermoplastic polyurethane from being denatured when the thermoplastic resin composition is prepared, the acid value of the methacrylic resin is preferably 0.2 mmol / g or less, more preferably 0.15 mmol / g or less, and even more preferably 0.1 mmol / g or less, and may be 0 mmol / g. The acid value can be measured by a titration method or the like described in JP-A-2005-23272. [ka] R 1 : Hydrogen atom, substituted or unsubstituted alkyl group having 1 to 6 carbon atoms R 2 : Hydrogen atom or t-butyl group
[0027] In the methacrylic resin (A) having a ring structure in the main chain, a vinyl monomer other than the vinyl monomers exemplified above may be appropriately added and copolymerized for the purpose of improving properties such as heat resistance, moldability, etc. The acrylic ester monomer copolymerizable with the methacrylic ester monomer and the vinyl monomer other than the acrylic ester monomers exemplified above may be used alone or in combination of two or more.
[0028] The total mass ratio of the methacrylic acid ester monomer unit (a1), the N-substituted maleimide monomer unit, and the styrene-based monomer in 100 mass% of the methacrylic resin (A) having a ring structure in its main chain is preferably 88 mass% or more, more preferably 94 mass% or more, and even more preferably 100 mass%, from the viewpoint of obtaining a molded product having even more excellent transparency and haze.
[0029] The content of the methacrylic resin (A) having a ring structure in the main chain in the thermoplastic resin composition of this embodiment may be 50 to 99% by mass relative to 100% by mass of the thermoplastic resin composition. From the viewpoint of obtaining a molded product excellent in transparency and toughness, the content is preferably 50 to 95% by mass, more preferably 55 to 95% by mass, and even more preferably 60 to 90% by mass. From the viewpoint of obtaining a molded product excellent in transparency, toughness, and scratch resistance, the content is further preferably 66 to 89% by mass, and particularly preferably 71 to 88% by mass.
[0030] (Weight average molecular weight) The weight average molecular weight (Mw) of the methacrylic resin (A) having a ring structure in the main chain contained in the methacrylic resin composition of this embodiment will be described. The methacrylic resin (A) having a ring structure in the main chain preferably has a weight average molecular weight (Mw) measured by GPC (gel permeation chromatography) of 50,000 or more and 250,000 or less. In order to obtain good mechanical strength and solvent resistance when made into a thermoplastic resin composition, the lower limit of the weight average molecular weight (Mw) of the methacrylic resin (A) having a ring structure in the main chain is preferably 50,000 or more, more preferably 70,000 or more, and even more preferably 85,000 or more. In order for the methacrylic resin composition to exhibit good fluidity, the upper limit of the weight average molecular weight (Mw) of the methacrylic resin (A) having a ring structure in the main chain is preferably 250,000 or less, more preferably 230,000 or less, and even more preferably 190,000 or less. When the weight-average molecular weight (Mw) of the methacrylic resin (A) having a ring structure in the main chain is in the range of 50,000 to 250,000, a thermoplastic resin composition can be obtained that has a good balance between flowability, mechanical strength, and solvent resistance, and maintains good moldability.
[0031] (molecular weight distribution) The molecular weight distribution (Mw / Mn) of the methacrylic resin (A) having a ring structure in the main chain contained in the methacrylic resin composition of this embodiment is 1.0 or more, and from the viewpoint of improving moldability, it is preferably 1.01 or more, preferably 6.0 or less, more preferably 5.5 or less, even more preferably 5.0 or less, and from the viewpoint of further improving moldability, it is particularly preferably 1.96 or less. When the molecular weight distribution (Mw / Mn) of the methacrylic resin (A) having a ring structure in the main chain is 1.0 or more and 6.0 or less, the physical properties exhibited by the methacrylic resin (A) having a ring structure in the main chain are stable.
[0032] Here, Mw represents the weight average molecular weight, and Mn represents the number average molecular weight. The weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin (A) having a ring structure in the main chain can be measured by GPC, specifically, by the method described in the examples described later. Specifically, a calibration curve is created from the elution time and weight average molecular weight using a standard methacrylic resin with a known monodisperse weight average molecular weight and an analytical gel column that elutes high molecular weight components first. Based on the calibration curve, the weight average molecular weight (Mw) and number average molecular weight (Mn) of the methacrylic resin (A) having a ring structure in the main chain of the specified measurement target can be calculated, and the molecular weight distribution (Mw / Mn) can be calculated from these. The number average molecular weight (Mn) is the simple average molecular weight per molecule and is defined as the total weight of the system / the number of molecules in the system. The weight average molecular weight (Mw) is defined as the average molecular weight by weight fraction.
[0033] (Unsaturated double bond terminal amount) The amount of unsaturated double bond terminals in the methacrylic resin (A) having a ring structure in the main chain is preferably 0.01 mol% or less, more preferably 0.009 mol% or less, and even more preferably 0.008 mol% or less, in order to effectively prevent yellowing of the thermoplastic resin composition caused by radicals generated by decomposition of the methacrylic resin (A) having a ring structure in the main chain causing decomposition or deterioration of the thermoplastic polyurethane (B) in the thermoplastic resin composition of this embodiment, and molding defects derived from monomers caused by decomposition of the thermoplastic resin composition. The amount of unsaturated double bond terminals can be controlled by controlling the polymerization temperature or by using a chain transfer agent. Specifically, in order to reduce the amount of unsaturated double bond terminals, when the methacrylic resin (A) having a ring structure in the main chain is produced by a suspension polymerization method, the polymerization temperature is preferably 80°C or less, more preferably 75°C or less, and even more preferably 70°C or less. The polymerization temperature may be constant, but it is also effective to reduce the amount of unsaturated double bond terminals by setting the polymerization temperature to 70°C or less at the beginning of the polymerization. As for the polymerization initiator, it is preferable to produce the polymerization initiator at 0.5% by mass or less, more preferably 0.3% by mass or less, even more preferably 0.25% by mass or less, and particularly preferably 0.23% by mass or less, based on 100% by mass of the methacrylic resin (A) having a ring structure in the main chain. When producing by a solution polymerization method, the polymerization temperature is preferably 185°C or less, more preferably 180°C or less, even more preferably 170°C or less, and particularly preferably 160°C or less. The polymerization initiator is preferably produced in an amount of 0.4% by mass or less, more preferably 0.2% by mass or less, even more preferably 0.15% by mass or less, and particularly preferably 0.1% by mass or less, based on 100% by mass of the methacrylic resin (A) having a ring structure in the main chain. The amount of unsaturated double bond terminals can be measured by the method described in the Examples below.
[0034] (Method for producing methacrylic resin (A) having a ring structure in the main chain) The methacrylic resin (A) having a ring structure in the main chain contained in the methacrylic resin composition of the present embodiment can be produced by, but is not limited to, a solution polymerization method, a bulk polymerization method, a cast polymerization method, or a suspension polymerization method. The preferred methods are bulk polymerization, solution polymerization, and suspension polymerization.
[0035] The polymerization temperature may be appropriately selected as the optimum polymerization temperature depending on the polymerization method, but is preferably 50°C or higher and 185°C or lower, more preferably 50°C or higher and 180°C or lower, and even more preferably 60°C or higher and 170°C or lower. By setting the polymerization temperature at 185°C or lower, the amount of unsaturated double bond terminals can be reduced, and yellowing of the thermoplastic resin composition and molding defects due to deterioration of the thermoplastic polyurethane (B) can be effectively prevented. In addition, by setting the temperature at 50°C or higher, the methacrylic resin can be produced with good productivity.
[0036] A polymerization initiator may be used when producing the methacrylic resin (A) having a ring structure in the main chain. The polymerization initiator is not limited to the following, but in the case of radical polymerization, for example, di-t-butyl peroxide, lauroyl peroxide, stearyl peroxide, benzoyl peroxide, t-butyl peroxy neodecanoate, t-butyl peroxy pivalate, dilauroyl peroxide, dicumyl peroxide, t-butyl peroxy-2-ethylhexanoate, 1,1-bis(t-butylperoxy)-3,3,5-trimethyl peroxide, t-butyl peroxy-2-ethylhexanoate ... Examples of the radical polymerization initiator include organic peroxides such as t-butylcyclohexane and 1,1-bis(t-butylperoxy)cyclohexane, and general azo-based radical polymerization initiators such as azobisisobutyronitrile, azobisisovaleronitrile, 1,1-azobis(1-cyclohexanecarbonitrile), 2,2'-azobis-4-methoxy-2,4-azobisisobutyronitrile, 2,2'-azobis-2,4-dimethylvaleronitrile, and 2,2'-azobis-2-methylbutyronitrile. These initiators may be used alone or in combination of two or more. These radical polymerization initiators may be used in combination with a suitable reducing agent as a redox-based initiator. These radical polymerization initiators and / or redox initiators are generally used in the range of 0 to 1 part by mass per 100 parts by mass of the total amount of all monomers used in the polymerization of the methacrylic resin (A) having a ring structure in the main chain, and can be appropriately selected in consideration of the temperature at which the polymerization is performed and the half-life of the polymerization initiator.
[0037] When bulk polymerization, cast polymerization, or suspension polymerization is selected as the polymerization method for the methacrylic resin (A) having a ring structure in the main chain, it is preferable to carry out the polymerization using a peroxide polymerization initiator from the viewpoint of preventing discoloration of the methacrylic resin (A) having a ring structure in the main chain. The peroxide polymerization initiator is not limited to the following, but examples thereof include lauroyl peroxide, decanoyl peroxide, and t-butylperoxy-2-ethylhexanoate, with lauroyl peroxide being more preferred.
[0038] When the methacrylic resin (A) having a ring structure in the main chain is polymerized by a solution polymerization method at a high temperature of 90°C or higher, it is preferable to use as the polymerization initiator a peroxide, an azobis initiator, or the like, which has a 10-hour half-life temperature of 80°C or higher and is soluble in the organic solvent used. Examples of the peroxide and azobis initiator include, but are not limited to, 1,1-bis(t-butylperoxy)-3,3,5-trimethylcyclohexane, cyclohexane peroxide, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, 1,1-azobis(1-cyclohexanecarbonitrile), and 2-(carbamoylazo)isobutyronitrile.
[0039] When producing the methacrylic resin (A) having a ring structure in the main chain, the molecular weight of the methacrylic resin (A) having a ring structure in the main chain may be controlled within a range that does not impair the object of the present invention. Methods for controlling the molecular weight of the methacrylic resin (A) having a ring structure in the main chain include, but are not limited to, the following, and include, for example, a method of controlling the molecular weight by using chain transfer agents such as alkyl mercaptans, dimethylacetamide, dimethylformamide, and triethylamine, and iniferters such as dithiocarbamates, triphenylmethylazobenzene, and tetraphenylethane derivatives. It is also possible to adjust the molecular weight by adjusting the amount of these additives.
[0040] As the chain transfer agent, from the viewpoint of handleability and stability, alkyl mercaptans are preferred. Examples of the alkyl mercaptans include, but are not limited to, n-butyl mercaptan, n-octyl mercaptan, n-dodecyl mercaptan, t-dodecyl mercaptan, n-tetradecyl mercaptan, n-octadecyl mercaptan, 2-ethylhexyl thioglycolate, ethylene glycol dithioglycolate, trimethylolpropane tris(thioglycolate), pentaerythritol tetrakis(thioglycolate), and the like.
[0041] These can be added appropriately depending on the molecular weight of the target methacrylic resin, but are generally used in the range of 0.001 parts by mass to 5 parts by mass per 100 parts by mass of the total amount of all monomers used in the polymerization of the methacrylic resin.
[0042] Other molecular weight control methods include changing the polymerization method, adjusting the amounts of the polymerization initiator, the chain transfer agent, the iniferter, etc., and changing various polymerization conditions such as the polymerization temperature.
[0043] These molecular weight control methods may be used alone or in combination of two or more.
[0044] <Thermoplastic polyurethane (B)> In this embodiment, the thermoplastic polyurethane (B) is contained in the thermoplastic resin composition. The thermoplastic polyurethane (B) contains a structural unit (b1) derived from a polyester polyol and a structural unit (b2) derived from an isocyanate having an alicyclic ring. In order to improve the transparency of the thermoplastic resin composition, when the total structural units derived from isocyanates contained in the thermoplastic polyurethane (B) are taken as 100% by mass, the mass ratio of the structural units derived from an isocyanate having one alicyclic ring is preferably 70% by mass or more. When the total structural units derived from isocyanates are taken as 100% by mass, the mass ratio of the structural units derived from an isocyanate having one alicyclic ring is more preferably 75% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and particularly preferably 100% by mass. The thermoplastic polyurethane (B) may be at least one type of thermoplastic polyurethane, and one type of thermoplastic polyurethane may be used alone, or two or more types of thermoplastic polyurethane may be used in combination.
[0045] Thermoplastic polyurethane (B) is usually produced by reacting the following components: (a) isocyanate, (b) compound reactive with isocyanate, and, optionally, at least one (c) catalyst and / or (d) conventional auxiliary and / or additive in the presence of the following components: (a) isocyanate and (b) compound reactive with isocyanate, called structural components. Methods for identifying these structural components include conventionally known methods, such as, but not limited to, the method described in the Journal of the Adhesion Society of Japan, Vol. 40, No. 6 (2004).
[0046] As the (a) isocyanate, from the viewpoint of transparency (high total light transmittance and low haze) and scratch resistance of the thermoplastic resin composition, it is preferable to use an isocyanate having an alicyclic ring in the structure, and it is more preferable to use an isocyanate having an alicyclic ring but no unsaturated carbon bond or aromatic ring. Although not limited to the following, specifically, 4,4-diisocyanatodicyclohexylmethane (H12MDI), 1,3-bisisocyanatomethylcyclohexane (XDI), and isophorone diisocyanate (IPDI) are preferable from the viewpoint of further excellent scratch resistance and transparency, and 1,3-bisisocyanatomethylcyclohexane (XDI) and isophorone diisocyanate (IPDI) are more preferable. The isocyanate may be an isocyanate having 5% by mass or less of a mixture or additive in the isocyanate, as long as it does not impair the effects of the present invention.
[0047] The number of alicyclic rings contained in the (a) isocyanate is preferably 1 to 4, and more preferably 1 in order to improve the heat distortion resistance, the transparency of the thermoplastic resin composition, and the yellowing resistance during thermal processing. In addition, when the (a) isocyanate contains multiple types of isocyanates having alicyclic rings, the number of alicyclic rings may be the number of alicyclic rings of the compound having the largest molar fraction among the compounds contained in the (a) isocyanate.
[0048] (b) As the compound having reactivity with isocyanate, at least one type of polyester polyol can be mentioned. By using the polyester polyol, the transparency of the thermoplastic resin composition becomes good. In the present invention, it is necessary that the structure of the thermoplastic polyurethane (B) contains a structural unit derived from the polyester polyol or a mixture of two or more of them. The polyester polyol includes a polycarbonate diol.
[0049] The mass proportion of the structural units derived from the polyester polyol in 100 mass% of the structural units derived from the polyol contained in the above thermoplastic polyurethane (B) is preferably 80 to 100 mass%, more preferably 90 to 100 mass%, and even more preferably 95 to 100 mass%. The mass proportion of polyether-derived structural units in 100 mass% of polyol-derived structural units contained in the above thermoplastic polyurethane (B) is preferably less than 5 mass%, more preferably less than 2 mass%, even more preferably less than 1 mass%, and it is particularly preferable that none is contained.
[0050] Examples of polyester polyols include polyester polyols produced from an organic dicarboxylic acid having 2 to 12 carbon atoms (preferably an aromatic dicarboxylic acid having 8 to 12 carbon atoms) and a polyhydric alcohol (preferably a diol having 2 to 12 carbon atoms, more preferably a diol having 2 to 6 carbon atoms). The organic dicarboxylic acids include succinic acid, glutaric acid, adipic acid, suberic acid, azelaic acid, sebacic acid, decanedicarboxylic acid, maleic acid, fumaric acid, phthalic acid, isophthalic acid, terephthalic acid, and isomers of naphthalenedicarboxylic acid. The dicarboxylic acids are used alone or in mixtures with other dicarboxylic acids. Instead of free dicarboxylic acids, corresponding dicarboxylic acid derivatives, such as dicarboxylic acid esters of alcohols having 1 to 4 carbon atoms, or dicarboxylic acid anhydrides, can also be used. The polyhydric alcohol is preferably a diol. The diol includes ethanediol, diethylene glycol, 1,2- and 1,3-propanediol, dipropylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,10-decanediol, glycerol, and trimethylolpropane, and is preferably ethylene glycol, 1,3-propanediol, methyl-1,3-propanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol, or 1,6-hexanediol. The polyhydric alcohol may be a polyester diol produced from a lactone (e.g., ε-caprolactone), or a hydroxycarboxylic acid (e.g., ω-hydroxycarboxylic acid, hydroxybenzoic acid).
[0051] In the production of polyester polyol, the reaction conditions of organic dicarboxylic acid and polyalcohol may be selected in such a way that the polyester polyol produced does not have free acid groups. The actual functional number of the polyester polyol produced is preferably 1.9 to 2.1, more preferably 2.0.
[0052] In the production of polyester polyols, a mixture of an organic dicarboxylic acid and a polyalcohol may be polycondensed in the presence or absence of a catalyst, preferably in the presence of a catalyst, more preferably in the presence of an esterification catalyst. In the production of the polyester polyol, a mixture of an organic dicarboxylic acid and a polyalcohol may be polycondensed under an atmosphere of an inert gas (eg, nitrogen, carbon monoxide, helium, argon, etc.). The temperature during the condensation polymerization of the organic dicarboxylic acid and the polyalcohol is preferably 150 to 250° C., more preferably 180 to 220° C. The condensation polymerization can be carried out under reduced pressure as desired. The condensation polymerization is typically continued until a desired acid number is reached (eg, an acid number of less than 10, preferably an acid number of less than 2). The molar ratio of the organic dicarboxylic acid to the polyalcohol used in the above condensation polymerization is preferably 1:1 to 1.8, and more preferably 1:1.05 to 1.2.
[0053] In particular, it is preferred that the thermoplastic polyurethane (B) contains structural units derived from a polyester polyol produced from ε-caprolactone and / or structural units derived from a condensate of adipic acid or sebacic acid with at least one polyhydric alcohol selected from the group consisting of ethylene glycol, 1,3-propanediol, methyl-1,3-propanediol, 1,4-butanediol, 3-methyl-1,5-pentanediol, and 1,6-hexanediol.
[0054] The number average molecular weight Mn of the polyester polyol used is preferably 500 to 4,000, more preferably 650 to 3,500, and further preferably 800 to 3,000. The number average molecular weight Mn can be measured by a GPC method.
[0055] (b) As a compound having reactivity with isocyanate, in addition to polyester polyol, polyhydric alcohol can be mentioned. Among polyhydric alcohols, at least one polyhydric alcohol selected from the group consisting of ethylene-1,2-diol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, 2,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, diethylene glycol, dipropylene glycol, 1,4-cyclohexanediol, 1,4-dimethanolcyclohexane, and neopentyl glycol is preferred. Polyhydric alcohols selected from the group consisting of ethylene-1,2-diol, 1,3-propanediol, 1,4-butanediol, and 1,6-hexanediol are more preferred. The polyhydric alcohol functions as a chain extender.
[0056] In the thermoplastic resin composition of the present embodiment, it is preferable that the thermoplastic polyurethane (B) contains a structural unit derived from at least one polyhydric alcohol selected from the group consisting of ethylene-1,2-diol, 1,3-propanediol, 1,4-butanediol, and 1,6-hexanediol as a polyol.
[0057] The (c) catalyst is preferably a (c) catalyst that accelerates the reaction between (a) the NCO group of the isocyanate and (b) the hydroxy group of the compound reactive to the isocyanate. The (c) catalyst includes tertiary amines, and is preferably triethylamine, dimethylcyclohexylamine, N-methylmorpholine, N,N'-dimethylpiperazine, 2-(dimethylaminoethoxy)ethanol or diazabicyclo[2.2.2]octane. The (c) catalyst is preferably an organometallic compound (e.g., titanate ester, iron compound (preferably iron(III) acetylacetonate), tin compound (preferably tin diacetate, tin dioctoate, tin dilaurate) or dialkyltin salt of aliphatic carboxylic acid (preferably dibutyltin diacetate, dibutyltin dilaurate), bismuth salt in which bismuth is preferably present in the oxidation state of 2 or 3, particularly 3).
[0058] The catalyst (c) is preferably a salt of a carboxylic acid. The carboxylic acid is preferably a carboxylic acid having 6 to 14 hydrocarbons, particularly preferably 8 to 12 hydrocarbons. The salt of a carboxylic acid is preferably a bismuth salt, and examples of suitable bismuth salts are bismuth (III) neodecanoate, bismuth 2-ethylhexanoate, and bismuth octanoate.
[0059] As the (c) catalyst used in the production of the thermoplastic polyurethane (B), a tin catalyst, particularly tin dioctoate, is preferably used, and the mass ratio is preferably 0.0001 to 0.1 parts by mass relative to 100 parts by mass of the (b) compound having reactivity with isocyanate. When a tertiary amine is used as the (c) catalyst, from the viewpoint of preventing the tertiary amine from being incorporated into the structural skeleton of the thermoplastic polyurethane (B) and yellowing during molding of the thermoplastic resin composition, the tertiary amine content in 100% by mass of the thermoplastic resin composition of this embodiment is preferably 0.9% by mass or less, more preferably 0.5% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably 0% by mass. In addition, from the viewpoint of preventing yellowing during molding, the content of the tertiary amine contained in 100% by mass of the thermoplastic polyurethane (B) is preferably 0.9% by mass or less, more preferably 0.5% by mass or less, even more preferably 0.1% by mass or less, and particularly preferably 0% by mass.
[0060] In producing the thermoplastic polyurethane (B), the ratio of the structural components (a) and (b) is preferably such that the equivalent ratio of the NCO groups of the isocyanate (a) to the total hydroxyl groups of the structural component (b) is 0.9 to 1.1: 1, more preferably 0.95 to 1.05: 1, and even more preferably 0.96 to 1.0: 1. The thermoplastic polyurethane (B) is preferably produced by reacting in the presence of a catalyst (c) and, optionally, an auxiliary and / or additive (d).
[0061] The content of the thermoplastic polyurethane (B) in the thermoplastic resin composition of this embodiment is 1 to 50 mass%, relative to 100 mass% of the thermoplastic resin composition. From the viewpoint of obtaining a molded article having good toughness and transparency, the content is preferably 5 to 50 mass%, more preferably 5 to 45 mass%, and even more preferably 10 to 40 mass%. From the viewpoint of obtaining a molded article having good toughness, transparency and scratch resistance, the content is further preferably 11 to 34 mass%, and particularly preferably 12 to 29 mass%.
[0062] In the thermoplastic resin composition of this embodiment, the total content of the methacrylic resin (A) having a ring structure in the main chain and the thermoplastic polyurethane (B) is preferably 80 mass% or more, more preferably 90 mass% or more, and even more preferably 100 mass%, relative to 100 mass% of the thermoplastic resin composition.
[0063] <Other ingredients> The thermoplastic resin composition of the present embodiment may contain other components in addition to the methacrylic resin (A) having a ring structure in the main chain and the thermoplastic polyurethane (B) as long as the effects of the present invention are not impaired. As the other components, other conventionally known resins can be mixed. The other resin is not particularly limited, and known curable resins and thermoplastic resins are suitably used. Examples of thermoplastic resins include, but are not limited to, polypropylene-based resins, polyethylene-based resins, polystyrene-based resins, syndiotactic polystyrene-based resins, ABS-based resins, methacrylic-based resins, AS-based resins, BAAS-based resins, MBS resins, AAS resins, biodegradable resins, polycarbonate-ABS resin alloys, polyalkylene arylate-based resins such as polybutylene terephthalate, polyethylene terephthalate, polypropylene terephthalate, polytrimethylene terephthalate, and polyethylene naphthalate, polyamide-based resins, polyphenylene ether-based resins, polyphenylene sulfide-based resins, and phenol-based resins. In particular, AS resin and BAAS resin are preferred for improving flowability, ABS resin and MBS resin are preferred for improving impact resistance, and polyester resin is preferred for improving chemical resistance. Furthermore, polyphenylene ether resins, polyphenylene sulfide resins, phenol resins, and the like have the effect of improving flame retardancy. Furthermore, examples of the curable resin include, but are not limited to, unsaturated polyester resin, vinyl ester resin, diallyl phthalate resin, epoxy resin, cyanate resin, xylene resin, triazine resin, urea resin, melamine resin, benzoguanamine resin, urethane resin, oxetane resin, ketone resin, alkyd resin, furan resin, styrylpyridine resin, silicone resin, synthetic rubber, and the like. These resins may be used alone or in combination of two or more kinds.
[0064] In order to impart various predetermined properties such as rigidity and dimensional stability to the thermoplastic resin composition of the present embodiment, various additives other than the methacrylic resin (A) having a ring structure in the main chain and the thermoplastic polyurethane (B) may be mixed within a range that does not impair the effects of the present invention. Examples of additives include, but are not limited to, plasticizers such as phthalate esters, fatty acid esters, trimellitate esters, phosphate esters, and polyesters; release agents such as higher fatty acids, higher fatty acid esters, and higher fatty acid mono-, di-, or triglycerides; antistatic agents such as polyethers, polyether esters, polyether ester amides, alkyl sulfonates, and alkylbenzene sulfonates; stabilizers such as phosphine stabilizers and light stabilizers; flame retardants; flame retardant assistants; curing agents; curing accelerators; conductivity imparting agents; stress relaxation agents; crystallization accelerators; dyes; hydrolysis inhibitors; lubricants; ultraviolet absorbers; antioxidants; impact resistance imparting agents; sliding improvers; compatibilizers; nucleating agents; reinforcing agents; reinforcing agents; flow adjusters; sensitizers; coloring pigments; rubber polymers; thickeners; anti-settling agents; anti-sagging agents; fillers; defoamers; coupling agents; rust inhibitors; antibacterial and anti-fungal agents; antifouling agents; conductive polymers; and carbon black. In particular, impact resistance agents such as acrylic rubber multilayer polymers and antioxidants are preferred.
[0065] <Antioxidants> The thermoplastic resin composition of the present invention and the molded article thereof preferably further contain an antioxidant. The antioxidant not only prevents the modification of a methacrylic resin composition having a ring structure in the main chain and the modification of a thermoplastic polyurethane resin composition, but also prevents the modification of a thermoplastic polyurethane resin composition caused by contact with a methacrylic resin composition having a ring structure in the main chain.
[0066] Examples of the antioxidant include hindered phenol-based antioxidants, amine-based antioxidants, phosphine-based antioxidants, phosphoric acid-based antioxidants, and sulfur-based antioxidants. Among these, from the viewpoint of effectively preventing the denaturation of the methacrylic resin composition and the infrared absorbing agent, it is more preferable to use phosphoric acid-based antioxidants and hindered phenol-based antioxidants, and it is even more preferable to use them in combination. It is preferable not to use phosphine-based antioxidants that generate toxic decomposition gases.
[0067] Examples of the phosphoric acid-based antioxidants include, but are not limited to, CAS Nos. 31570-04-4, 3806-34-6, 26741-53-7, 119345-01-6, 203255-81-6, 145650-60-8, 52664-24-1, 80693-00-1, 126050-54-2, 80410-33-9, and 154862-43-8.
[0068] The phosphoric acid antioxidant preferably has two or more aromatic rings directly bonded to oxygen atoms, and the two or more aromatic rings directly bonded to oxygen atoms are bonded to each other directly or via -(CH2)n- (n is an integer of 1 to 4, preferably 1 to 2). When such a phosphoric acid antioxidant is used in combination with a hindered phenol antioxidant, it exhibits a remarkable effect of suppressing the oxidative deterioration of the infrared absorbing agent, and can suppress the oxidative deterioration of the hindered phenol antioxidant. It can also suppress the denaturation of the infrared absorbing agent even when exposed to a high temperature environment or a high temperature and high humidity environment for a long period of time, and can maintain the infrared absorbing ability for a long period of time. The aromatic ring includes aromatic hydrocarbon groups or heteroaromatic groups having 3 to 16 carbon atoms, preferably 3 to 6 carbon atoms. Specific examples of the aromatic ring include aromatic hydrocarbon groups such as a phenyl group, a naphthyl group, a pyrenyl group, a phenanthrenyl group, and an anthracenyl group; and heteroaromatic groups such as an imidazole group, a pyrazole group, an oxazole group, a thiazole group, a pyrazine group, a pyridyl group, a quinoline group, and an isoquinoline group. Specific product names of the phosphoric acid-based antioxidants having two or more aromatic rings directly bonded to oxygen atoms, in which the two or more aromatic rings directly bonded to the oxygen atoms are bonded to each other directly or via -(CH2)n- (n is an integer of 1 to 4), include Adeka STAB HP-10 manufactured by Adeka, Sumilizer GP manufactured by Sumitomo Chemical, Irgafos 12 manufactured by BASF, and HCA manufactured by Sanko.
[0069] The melting point (Tm) of the phosphoric acid-based antioxidant is preferably 50° C. or higher, more preferably 93° C. or higher, even more preferably 96° C. or higher, and even more preferably 100° C. or higher, from the viewpoint of achieving good dispersibility. Also, the melting point is preferably 280° C. or lower, more preferably 250° C. or lower, and even more preferably 230° C. or lower.
[0070] From the viewpoint of effectively preventing the denaturation of the infrared absorbing agent, the content of the phosphoric acid antioxidant is preferably 0.03 parts by mass or more, more preferably 0.05 parts by mass or more, and even more preferably 0.06 parts by mass or more, relative to 100 parts by mass of the methacrylic resin. From the viewpoint of preventing mold contamination due to bleeding out of the methacrylic resin composition, the content of the phosphoric acid antioxidant is preferably 0.5 parts by mass or less, more preferably 0.45 parts by mass or less, even more preferably 0.3 parts by mass or less, and even more preferably 0.2 parts by mass or less, relative to 100 parts by mass of the methacrylic resin.
[0071] Examples of the hindered phenol-based antioxidants include, but are not limited to, CAS Nos. 96-69-5, 6683-19-8, 2082-79-3, 90498-90-1, 79-74-3, 1879-09-0, 85-60-9, 119-47-1, 36443-68-2, 68610-51-5, 61167-58-6, 123968-25-2, 991-84-4, 40601-76-1, 27676-62-6, 1709-70-2, 32687-78-8, 41484-35-9, 23128-74-7, 35074-77-2, and 35958-30-6.
[0072] In addition, the hindered phenol-based antioxidant is preferably one having at least one ring structure (5-membered ring, 6-membered ring, etc.) containing 1 to 3, preferably 2 to 3, heteroatoms such as oxygen or nitrogen atoms in the molecule. When such a hindered phenol-based antioxidant is used in combination with a phosphoric acid-based antioxidant, the effect of suppressing the oxidative deterioration of the phosphoric acid-based antioxidant becomes significant, and even if it is exposed to a high temperature environment or a high temperature and high humidity environment for a long time, it can suppress the denaturation of the infrared absorbing agent and maintain the infrared absorbing ability. Specific product names of hindered phenol-based antioxidants having at least one ring structure containing a heteroatom such as an oxygen atom or a nitrogen atom in the molecule include, for example, Sumilizer GA-80 manufactured by Sumitomo Chemical, Adeka STAB AO-80 manufactured by Adeka, Adeka STAB AO-20 manufactured by Adeka, Irganox 565 manufactured by BASF, SONGNOX 1790 manufactured by SONGWON, and SONGNOX 3114 manufactured by SONGWON.
[0073] From the viewpoint of achieving good dispersibility, the melting point (Tm) of the hindered phenol-based antioxidant is preferably 50° C. or higher, more preferably 93° C. or higher, even more preferably 96° C. or higher, and even more preferably 100° C. or higher. In addition, the melting point is preferably 280° C. or lower, more preferably 250° C. or lower, and even more preferably 230° C. or lower.
[0074] The content of the hindered phenol-based antioxidant is preferably 0.02 parts by mass or more, more preferably 0.04 parts by mass or more, and even more preferably 0.05 parts by mass or more, relative to 100 parts by mass of the methacrylic resin, from the viewpoint of effectively suppressing the deterioration of the phosphoric acid-based antioxidant and the infrared absorbing agent. Also, the content of the hindered phenol-based antioxidant is preferably 0.4 parts by mass or less, more preferably 0.35 parts by mass or less, even more preferably 0.3 parts by mass or less, and even more preferably 0.2 parts by mass or less, relative to 100 parts by mass of the methacrylic resin, from the viewpoint of suppressing coloration of the resin composition.
[0075] From the viewpoint of suppressing denaturation of the infrared absorbent, it is preferable that the melting points (Tm) of the ultraviolet absorbent, the phosphoric acid-based antioxidant and the hindered phenol-based antioxidant are all 50° C. or higher. When the melting points of the ultraviolet absorber, the phosphoric acid antioxidant, and the hindered phenol antioxidant are 50° C. or higher, when dispersing other components in the methacrylic resin by thermal melting in the production of the methacrylic resin composition of this embodiment, the viscosity does not decrease more than necessary, and good dispersibility can be achieved, and the deterioration of the infrared absorber can be more effectively suppressed. From the same viewpoint, the melting points of the ultraviolet absorber, the phosphoric acid antioxidant, and the hindered phenol antioxidant are more preferably 93° C. or higher, more preferably 96° C. or higher, and even more preferably 100° C. or higher. In addition, it is preferably 280° C. or lower, more preferably 250° C. or lower, and even more preferably 230° C. or lower.
[0076] The content of the above-mentioned other components in the thermoplastic resin composition for obtaining the molded article made of the thermoplastic resin composition of the present embodiment is preferably 0 to 40 mass%, more preferably 0.01 to 30 mass%, and even more preferably 0.02 to 25 mass%, relative to 100 mass% of the thermoplastic resin composition, in order to maintain the transparency of the thermoplastic resin composition and prevent molding defects such as bleed-out. By containing them in the above ranges, the functions of each material can be exhibited. In order to effectively impart impact resistance while ensuring transparency, the impact resistance imparting agent is preferably used in an amount of 3 to 50 mass%, more preferably 5 to 20 mass%, and even more preferably 5 to 9 mass%, relative to 100 mass% of the thermoplastic resin composition.
[0077] The thermoplastic resin composition of the present embodiment, when formed into a flat plate sample, preferably has a total light transmittance of 89% or more, more preferably 90% or more, and even more preferably 91% or more. The total light transmittance can be adjusted, for example, by setting the mass ratio of the methacrylic resin (A) having a ring structure in its main chain and the thermoplastic polyurethane (B) to the preferred range described above, by using the preferred example of the methacrylic resin (A) having a ring structure in its main chain described above, or by other means. The total light transmittance can be measured by the method described in the Examples section below.
[0078] The thermoplastic resin composition of the present embodiment, when formed into a flat plate sample, preferably has a haze of 10% or less, more preferably 9% or less, further preferably 8% or less, and particularly preferably 3.5% or less. The haze can be adjusted, for example, by setting the mass ratio of the methacrylic resin (A) having a ring structure in its main chain and the thermoplastic polyurethane (B) to the preferred range described above, by using the preferred example of the methacrylic resin (A) having a ring structure in its main chain described above, or the like. The haze can be measured by the method described in the Examples below.
[0079] <Method of producing thermoplastic resin composition> The thermoplastic resin composition can be obtained by mixing and kneading a methacrylic resin (A) having a ring structure in the main chain, a thermoplastic polyurethane (B), and, if necessary, the various additives and other resins described above. For example, the composition can be produced by kneading using a kneading machine such as an extruder, a heating roll, a kneader, a roller mixer, or a Banbury mixer. In particular, kneading with an extruder is preferred from the viewpoint of productivity. The kneading temperature (i.e., the temperature when the methacrylic resin (A) having a ring structure in the main chain and the thermoplastic polyurethane (B) are mixed) is preferably 170°C or higher, more preferably 180°C or higher, and even more preferably 200°C or higher, from the viewpoint of productivity. Moreover, from the viewpoint of preventing deterioration of the methacrylic resin (A) having a ring structure in the main chain and the thermoplastic polyurethane (B) and volatilization of various additives, it is preferably 290°C or lower, more preferably 280°C or lower, and even more preferably 260°C or lower. In the present embodiment, the kneading temperature refers to the set temperature at the center of the cylinder when an extruder is used.
[0080] <Molded body> The molded article of the present embodiment is characterized by containing the thermoplastic resin composition of the present embodiment. The molded article may be an injection molded article.
[0081] <Method of manufacturing molded body> The molded article of the present embodiment can be produced by a known molding method. Known molding methods include, but are not limited to, injection molding, extrusion molding, blow (hollow) molding, vacuum molding, compression molding, calendar molding, inflation molding, etc. In particular, molding by injection molding is preferred from the viewpoint of productivity. From the viewpoint of productivity, the molding temperature is preferably 170° C. or higher, more preferably 190° C. or higher, and even more preferably 200° C. or higher. From the viewpoint of preventing deterioration of the methacrylic resin (A) having a ring structure in the main chain and the thermoplastic polyurethane (B) and volatilization of various additives, the molding temperature is preferably 290° C. or lower, more preferably 280° C. or lower, and even more preferably 260° C. or lower. From the viewpoint of productivity, the cylinder temperature during molding is preferably 170° C. or higher, more preferably 190° C. or higher, and even more preferably 200° C. or higher. From the viewpoint of preventing deterioration of the methacrylic resin (A) having a ring structure in the main chain and the thermoplastic polyurethane (B) and volatilization of various additives, the cylinder temperature is preferably 290° C. or lower, more preferably 280° C. or lower, and even more preferably 260° C. or lower.
[0082] <Applications of molded products> The molded article containing the thermoplastic resin composition of the present embodiment has good weather resistance, scratch resistance, and transparency, and can have excellent long-term stability against an outdoor environment exposed to ultraviolet rays. Therefore, the molded article can be suitably used for vinyl house films, liquid crystal protective films, building materials, vehicle materials, electrical and electronic materials, lighting materials, etc. Specific applications of the molded article of the present embodiment include, for example, roofing materials used in buildings, automobiles, trains, or buses, protective materials used in lighting, signs, and meters, vehicle lighting materials, ship lighting materials, battery protective covers, etc. It is particularly preferable to use the molded article as a vehicle material or a vehicle lighting material.
[0083] Further embodiments of the invention can be found in the claims and examples. The above-mentioned features of the articles, methods and methods of use according to the invention and the features described below can of course be used not only in the respective combinations described, but also in other combinations without going beyond the scope of the invention. Thus, for example, the invention also implicitly includes combinations of preferred features with particularly preferred features, or combinations of features not specifically characterized with particularly preferred features, etc., even if the combinations are not explicitly described. EXAMPLES
[0084] Examples of the invention are given below which are not limiting, and in particular the invention also includes embodiments resulting from combinations thereof.
[0085] [Raw materials used in the examples and comparative examples] <Raw materials for methacrylic resin (A) having a ring structure in the main chain> The raw materials for methacrylic resin (A) having a ring structure in the main chain used in the production of the thermoplastic resin composition are as follows. · Methyl methacrylate (MMA): Manufactured by Asahi Kasei (with 2.5 mass ppm of 2,4-dimethyl-6-t-butylphenol manufactured by Chugai Boeki added as a polymerization inhibitor) · Styrene: Manufactured by Asahi Kasei · Maleic anhydride (MAH): Manufactured by Nippon Shokubai · N-Cyclohexyl maleimide: Manufactured by Nippon Shokubai · n-Octyl mercaptan: Manufactured by Arkema · Lauroyl peroxide: Manufactured by NOF Corporation · Calcium tertiary phosphate: Manufactured by Nippon Chemical Industry Co., Ltd., used as a suspending agent · Calcium carbonate: Manufactured by Shiraishi Kogyo Co., Ltd., used as a suspending agent · Sodium lauryl sulfate: Manufactured by Wako Pure Chemical Industries, Ltd., used as a suspending aid
[0086] <Thermoplastic polyurethane (B)> · Estane NY5685N00A: Polyurethane 1 manufactured by F. C. I. · Fortimo XCT-A1095: Polyurethane 2 manufactured by Mitsui Chemicals
[0087]
Table 1
[0088] <Additives> · Tinuvin P: Manufactured by BASF, melting point 128 °C · Stearamide: Neutron-2 manufactured by Nippon Seika Chemical Co., Ltd.
[0089] [Measurement and evaluation methods] <I. Measurement of the molecular weight of methacrylic resin (A) having a ring structure in the main chain> The weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) (Mn is the number average molecular weight) of the methacrylic resin (A) having a ring structure in the main chain were measured using the following apparatus and conditions. Measurement equipment: Tosoh Corporation gel permeation chromatography (HLC-8320GPC) Measurement conditions: Columns: One TSKguardcolumn SuperH-H, two TSKgel SuperHM-M, and one TSKgel SuperH2500 were used, connected in series. With this column, high molecular weight molecules elute early, and low molecular weight molecules elute slowly. Detector: RI (differential refractometer) detector Detection sensitivity: 3.0mV / min Column temperature: 40℃ Sample: 0.02 g of methacrylic resin in 20 mL of tetrahydrofuran Injection volume: 10μL Developing solvent: tetrahydrofuran, flow rate: 0.6 mL / min, 2,6-di-t-butyl-4-methylphenol (BHT) was added at 0.1 g / L as an internal standard. As standard samples for the calibration curve, the following ten types of polymethyl methacrylate (PMMA Calibration Kit MM-10, manufactured by Polymer Laboratories) with known monodisperse peak molecular weights and different molecular weights were used. In addition, since the polymethyl methacrylates of the standard specimens used for the standard samples for the calibration curve each had a single peak, the corresponding peaks were expressed as weight peak molecular weights Mp, which was distinguished from the peak top molecular weights calculated when a sample had multiple peaks. Weight peak molecular weight (Mp) Standard sample 1 1,916,000 Standard sample 2 625,500 Standard sample 3 298,900 Standard sample 4 138,600 Standard sample 5 60,150 Standard sample 6 27,600 Standard sample 7 10,290 Standard sample 8 5,000 Standard sample 9 2,810 Standard material 10 850 Under the above conditions, the RI detection intensity with respect to the elution time of the methacrylic resin (A) having a ring structure in the main chain was measured. Based on the area of the GPC elution curve and the calibration curve of the cubic approximation formula, the weight average molecular weight (Mw) and molecular weight distribution (Mw / Mn) of the methacrylic resin (A) having a ring structure in the main chain were determined.
[0090] <II. Analysis of the structural unit of the methacrylic resin (A) having a ring structure in the main chain> 1 The structural unit was identified by 1H-NMR measurement, and its abundance (mass %) was calculated. 1 The measurement conditions for 1H-NMR measurement are as follows. Apparatus: JEOL-ECA500 Solvent: CDCl3-d1 (deuterated chloroform) Sample: 1 g of methacrylic resin (A) was dissolved in 10 ml of acetone, 20 ml of methanol was added dropwise and filtered. 15 mg of the insoluble matter dried in vacuo at 40 °C for 15 hours was dissolved in 0.75 mL of CDCl3-d1 to obtain a sample for measurement.
[0091] <III. Unsaturated double bond end amount of the methacrylic resin (A) having a ring structure in the main chain> 1 The structural unit was identified by 1H-NMR measurement, and the abundance (mol %) in the methacrylic resin (A) having a ring structure in the main chain was calculated. The unsaturated double bond end amount was calculated from the integral value of the unsaturated double bond end peak (5.4 to 5.6 ppm) and the peak integral value of the methyl group bonded to the oxygen atom of the ester group of the methacrylic resin (A) having a ring structure in the main chain (3.6 ppm). 1 The measurement conditions for 1H-NMR measurement are as follows. Apparatus: JEOL-ECA500 Number of scans: 5000 times Measurement temperature: room temperature Observed nucleus: 1H (500 MHz) Solvent: CDCl3-d1 (deuterated chloroform) Sample: 1 g of methacrylic resin (A) was dissolved in 10 ml of chloroform, 20 ml of methanol was added dropwise, and the solution was filtered. The insoluble matter after filtration was dissolved again in 10 ml of chloroform, 20 ml of methanol was added dropwise, and the filtration was repeated twice. The remaining insoluble matter was vacuum dried at 40°C for 15 hours, and 75 mg of the solution was dissolved in 10.75 mL of CDCl3-d to prepare the measurement sample. If the insoluble matter after the final filtration did not reach 75 mg, the above procedure was repeated until it reached 75 mg.
[0092] (Elemental analysis) The monomer units of the methacrylic resin A-1 in Production Example A1 described later were identified by elemental analysis. Sample: 1g of methacrylic resin was dissolved in 10ml of acetone, 20ml of methanol was dropped, and the mixture was filtered. The insoluble matter was vacuum dried at 40℃ for 15 hours, leaving 7.5mg of the sample, which was collected in a platinum pan and measured twice under the following measurement conditions using a Mitsubishi Chemical Analytech TN-110. The average value of the two measurements was taken as the total nitrogen content. The sample container (platinum pan) used was one that had been pre-inserted into the apparatus and pre-baked. The CMI monomer unit content (wt%) and MMA monomer unit content (wt%) in the polymer were calculated from the measured total nitrogen content according to the following formulas (A) and (B). Measurement conditions Temperature: Pyrolysis furnace 800℃, oxidation furnace 900℃ Carrier gas: O2 (300mL / min.), Ar / O2 (400mL / min.) Standard sample: Pyridine / toluene solution Detector: Reduced pressure chemiluminescence detector Range: Low [Total nitrogen content] × (Molecular weight of CMI: 179 / Molecular weight of nitrogen: 14) = [Content of CMI monomer units (wt%)] Formula (A) 100(wt%) - [CMI monomer unit content (wt%)] = [MMA monomer unit content (wt%)] Equation (B) The monomer unit of the methacrylic resin A-2 in Production Example A2 described later is expressed by the formula (B): 100 (wt%) - [CMI monomer unit content (wt%)] = [MMA monomer unit + styrene monomer unit content (wt%)] ··· formula (B), and the ratio of each component in [MMA monomer unit + styrene monomer unit content (wt%)] is as described above. 1 The amount was determined from the results of structural unit analysis by H-NMR measurement.
[0093] <Measurement of total light transmittance> The total light transmittance of a 2 mm thick flat plate sample obtained using the method described below was measured in accordance with JIS K7361 using a Nippon Denshoku NDH7000. Total light transmittance of 91% or more was rated "+++" (exceptionally excellent), 90% or more was rated "++" (good), 89% or more was rated "+" (level acceptable for practical use), and less than 89% was rated "NG" (poor).
[0094] <Haze measurement> The haze of a 2 mm thick plate sample obtained by the method described below was measured in accordance with JIS K7136 using NDH7000 manufactured by Nippon Denshoku. To judge the haze, the haze of a 2 mm thick flat plate sample obtained by the method described below was used as the haze of the thermoplastic resin composition. If the haze value was 1.5% or less, it was rated as "+++" (particularly excellent), if it was more than 1.5% and less than 2.2%, it was rated as "++" (excellent), if it was more than 2.2% but not more than 2.5%, it was rated as "+" (a level that is acceptable for practical use), and if it was more than 2.5%, it was rated as "NG" (poor).
[0095] <Evaluation of toughness> The JIS type A1 dumbbell-shaped multipurpose test piece obtained in the "dumbbell-shaped multipurpose test piece" described later was subjected to a tensile test in accordance with ISO527-1 (JIS K7161-1). For the test, an autograph AGS-5kNX manufactured by Shimadzu Corporation was used. The tensile fracture strain or nominal tensile fracture strain was measured five times with a gauge length of 75 mm, and the average value was used as an index of toughness. If the tensile fracture strain or nominal tensile fracture strain was 9% or more, it was rated as "++" (excellent), if it was 5% or more but less than 9%, it was rated as "+" (sufficient for practical use), and if it was less than 5%, it was rated as "NG" (poor).
[0096] <Evaluation of yellowing resistance> The pellets of the thermoplastic resin composition were put into an injection molding machine (Toshiba Machine EC-100SX) with the temperature of the center of the cylinder set to 220°C and the mold temperature set to 50°C, and six 100 mm square flat plates with a thickness of 2 mm were molded and discarded. The yellowness of each of the seventh to eleventh plates was measured and the average value YI1 was obtained. The molding cycle was set to 65 seconds. Next, the pellets were put into an injection molding machine (Toshiba Machine EC-100SX) with the temperature of the center of the cylinder set to 250°C and the mold temperature set to 50°C, and six 100 mm square flat plates with a thickness of 2 mm were molded and discarded. The yellowness of each of the seventh to eleventh plates was measured and the average value YI2 was obtained. The molding cycle was set to 65 seconds. ΔYI was calculated from YI2-YI1, and used as an index of thermal stability, and yellowing resistance was evaluated according to the following criteria: ΔYI≦0.5:+++ (excellent), 0.5<ΔYI<1.5:++ (good), 1.5≦ΔYI≦2.0:+ (sufficient thermal stability for practical use), ΔYI<2.0:NG (poor). This evaluation allows the difference in yellowness depending on the molding temperature conditions to be understood, and allows the degree of freedom in setting molding conditions to be evaluated when attempting to thermally process the thermoplastic resin composition of this embodiment. The yellowness was measured using a Nippon Denshoku COH-7700 in accordance with JIS K7373 under a C light source and a 2° visual field transmission mode.
[0097] <Evaluation of processing stability> Pellets of the thermoplastic resin composition were placed in an injection molding machine (Toshiba Machine EC-100SX) with the cylinder center temperature set at 260°C, mold temperature set at 50°C, injection speed set at 30mm / sec, and molding cycle set at 65 sec, and 50 100mm square flat plates with a thickness of 2mm were molded. The number of plates with silver defects was counted and used as an index of thermal processing stability. The processing stability during heat processing was evaluated based on the following criteria: ++ (good) when the number of silver spots was 3 or less, + (sufficient for practical use) when the number of silver spots was 7 or less, and NG (bad) when the number of silver spots was 8 or more. This evaluation allows the evaluation of continuous moldability (productivity) under relatively high molding temperature conditions when attempting to heat process the thermoplastic resin composition of this embodiment.
[0098] The thermoplastic resin composition of the present embodiment can be analyzed by the following method to determine the mass ratio of the methacrylic resin (A) having a ring structure in the main chain and the thermoplastic polyurethane (B) in the thermoplastic resin composition. 400 mg of the thermoplastic resin composition is dissolved in 40 mL of tetrahydrofuran. The solution phase contains a methacrylic resin (A) having a ring structure in the main chain, and the swelling layer contains a thermoplastic polyurethane (B). The solution phase is separated by filtration, and the reprecipitated product is dissolved again in 40 mL of tetrahydrofuran and reprecipitated with 350 mL of methanol. This is dried at 60°C under nitrogen blowing to obtain sample A, and its mass is measured. 2 mg of dimethyl sulfone standard substance is added to 10 mg of sample A as a standard substance, and the mixture is dissolved in 1 mL of CDCl3-d1 to obtain measurement sample 1. 1 The mass of the methacrylic resin (A) having a ring structure in the main chain in 10 mg of sample A is quantified by H-NMR measurement (ECA-500 manufactured by JEOL Ltd.). The mass ratio of the methacrylic resin in 10 mg of sample A is applied to sample A to obtain the mass ratio of the methacrylic resin in the thermoplastic resin composition. At this time, the structure of the methacrylic resin (A) having a ring structure in the main chain can also be identified. In addition, the mass of the swollen layer was measured for sample B, which was dried at 60°C under nitrogen blowing. 2 mg of bistrimethylsilylbenzene-d4 standard substance was added to 10 mg of sample B, and the mixture was dissolved in 1 mL of deuterated dimethylformamide to obtain measurement sample 2. 1 The mass of thermoplastic polyurethane (B) in 10 mg of sample B is quantified by H-NMR measurement (ECA-500 manufactured by JEOL Ltd.). The mass ratio of the thermoplastic polyurethane in 10 mg of sample B is applied to sample B to determine the mass ratio of the thermoplastic polyurethane (B) in the thermoplastic resin composition. At this time, the structure of the thermoplastic polyurethane (B) can also be identified. If the detailed composition of thermoplastic polyurethane (B) is unclear, the composition can be identified by using IR measurement and pyrolysis GC / MS measurement in combination. In IR measurement, the frozen and crushed sample B is mixed with KBr and made into a tablet, and the IR measurement is performed to identify the composition of thermoplastic polyurethane (B). In pyrolysis GC / MS measurement, 25.0 mg of octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is collected in a 100 mL volumetric flask. Dimethylformamide is added to the measuring flask up to the mark line to prepare a 0.025 mass% octadecyl 3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate standard solution. 1 mL of the standard solution is added to sample B and dissolved to prepare the solution for pyrolysis GC / MS measurement. The pyrolysis GC / MS measurement is performed using a double-shot pyrolyzer, with the first step being thermal extraction at 300°C, and the second step being pyrolysis at 500°C, followed by pyrolysis GC / MS measurement to identify the composition of thermoplastic polyurethane (B).
[0099] The acid value of the methacrylic resin (A) of this embodiment can be measured by the following method. Specifically, 0.3 g of a polymer sample is dissolved in a mixed solvent of 37.5 ml of methylene chloride and 37.5 ml of methanol. Two drops of phenolphthalein ethanol solution are added, and then 5 ml of 0.1 N aqueous sodium hydroxide solution is added. The excess base is titrated with 0.1 N hydrochloric acid, and the acid value can be calculated as the difference in milliequivalent between the added base and the hydrochloric acid used until neutralization is achieved.
[0100] [Thermoplastic resin composition] In the examples and comparative examples described later, the methacrylic resin (A) having a ring structure in the main chain used as a constituent component of the thermoplastic resin composition will be described below.
[0101] <Methacrylic resin (A) having a ring structure in the main chain> As the methacrylic resin (A) having a ring structure in the main chain, methacrylic resins (A-1) to (A-3) produced in the following Production Examples A1 to A3 were used.
[0102] (Production Example A1 (Production of Methacrylic Resin (A-1))) Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid (a). Next, 26 kg of ion-exchanged water was added to a 60 L reactor and heated to 80° C., and 20 kg of a monomer mixture prepared in advance by mixing the mixed liquid (a), 93 parts by mass of methyl methacrylate, 6.5 parts by mass of N-cyclohexylmaleimide, 0.2 parts by mass of lauroyl peroxide, and 0.3 parts by mass of n-octyl mercaptan was added. Thereafter, suspension polymerization was carried out while maintaining the initial polymerization temperature at about 75° C., and after observing an exothermic peak, the temperature was raised to 96° C. at a rate of 1° C. / min, and the mixture was aged for 100 minutes, after which the polymerization reaction was essentially completed. Next, the mixture was cooled to 50°C, and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh to remove aggregates, and the resulting bead-like polymer was washed, dehydrated, and dried to obtain polymer microparticles 1. The polymer microparticles 1 were pelletized using a φ26 mm twin-screw extruder set at 240°C to obtain "methacrylic resin (A-1)". The weight-average molecular weight of the resulting resin was 101,000, the molecular weight distribution (Mw / Mn) was 1.9, the structural unit was MMA / N-cyclohexylmaleimide=93.7 / 6.3% by mass, the oxidation was 0.1 mmol / g or less, and the amount of unsaturated double bond terminals was 0.003 mol%.
[0103] (Production Example A2 (Production of Methacrylic Resin (A-2))) Into a vessel equipped with a stirrer were placed 2 kg of ion-exchanged water, 65 g of tribasic calcium phosphate, 39 g of calcium carbonate, and 0.39 g of sodium lauryl sulfate to obtain a mixed liquid (a). Next, 26 kg of ion-exchanged water was added to a 60 L reactor and the temperature was raised to 80° C., and 20 kg of a monomer mixture prepared in advance by mixing the mixed liquid (a), 87 parts by mass of methyl methacrylate, 6.5 parts by mass of N-cyclohexylmaleimide, 6 parts by mass of styrene, 0.2 parts by mass of lauroyl peroxide, and 0.3 parts by mass of n-octyl mercaptan was added. Thereafter, suspension polymerization was carried out while maintaining the initial polymerization temperature at about 80° C., and after observing an exothermic peak, the temperature was raised to 96° C. at a rate of 1° C. / min, and the mixture was aged for 100 minutes, after which the polymerization reaction was essentially completed. Next, the mixture was cooled to 50°C, and 20% by mass of sulfuric acid was added to dissolve the suspending agent. The polymerization reaction solution was then sieved through a 1.68 mm mesh to remove aggregates, and the resulting bead-like polymer was washed, dehydrated, and dried to obtain polymer microparticles 1. The polymer microparticles 2 were pelletized using a φ26 mm twin-screw extruder set at 240°C to obtain "methacrylic resin (A-2)". The weight-average molecular weight of the resulting resin was 103,000, the molecular weight distribution (Mw / Mn) was 1.9, the structural unit was MMA / N-cyclohexylmaleimide / styrene=87.5 / 6.5 / 6% by mass, the oxidation was 0.1 mmol / g or less, and the amount of unsaturated double bond terminals was 0.006 mol%.
[0104] (Production Example A3 (Production of Methacrylic Resin (A-3)) Using a vessel equipped with a stirrer, 95 parts by mass of methyl methacrylate, 5 parts by mass of maleic anhydride, 0.05 parts by mass of lauroyl peroxide, and 0.25 parts by mass of n-octyl mercaptan were added and dissolved to prepare a monomer mixture liquid. Meanwhile, a cell was prepared by assembling two glass plates measuring 250 × 300 mm and 6 mm thick, with a flexible polyvinyl chloride gasket attached around their outer periphery so that the distance between the two glass plates was 3.5 mm. The above-mentioned monomer mixture liquid was subjected to a volatilization operation for 2 minutes under a reduced pressure of 50 torr while being stirred. Thereafter, the reduced pressure was released, the pressure was returned to normal, and the mixture was immediately poured into the glass cell to fill it. Next, the resin was kept in a hot water bath adjusted to 60-65°C for 22 hours, and then in a hot air circulating oven adjusted to 110°C for 3 hours. The resin was then allowed to cool indoors, and the glass plate was removed to obtain a resin sheet. The sheet-like resin obtained as described above was pulverized with a coarse pulverizer, Orient Mill VM-42D, manufactured by Seishin Enterprise Co., Ltd., equipped with a 10 mm mesh screen, and then the pulverized material was sieved through a 500 μm sieve to remove fine powder and obtain a pulverized composition. This pulverized composition was pelletized with a φ26 mm twin-screw extruder set at 240 ° C to obtain "methacrylic resin (A-6)". The weight-average molecular weight of the obtained resin was 108,000, the molecular weight distribution (Mw / Mn) was 1.92, the structural unit was MMA / MAH=95.2 / 4.8 mass%, the amount of unsaturated double bond terminals was 0.004 mol%, and the oxidation was 0.22 mmol / g.
[0105] [Examples 1 to 7, Comparative Example 1] Methacrylic resin (A) having a ring structure in the main chain, thermoplastic polyurethane (B), 0.1 parts by mass of ADK STAB HP-10, 0.1 parts by mass of Irganox 1076, and other additives were weighed out so as to obtain the blending ratios shown in Table 2, and then charged into a tumbler and mixed. After thorough mixing, the mixed raw materials were charged into a φ26mm twin-screw extruder, melt-kneaded (compounded) to generate strands, cooled in a water bath, and cut with a pelletizer to obtain pellets. During compounding, a vacuum line was connected to the vent of the extruder, and volatile components such as moisture and monomer components were removed under conditions of -0.04 MPa. Thus, a thermoplastic resin composition was obtained. The kneading temperature of the thermoplastic resin composition was 230°C. The values in Table 2 represent the number of blended parts (parts by mass) when the total mass of the methacrylic resin (A) having a ring structure in the main chain and the thermoplastic polyurethane (B) is taken as 100 parts by mass. The mass proportions of the methacrylic resin (A) having a ring structure in the main chain and the mass proportions of the thermoplastic polyurethane (B) in the thermoplastic resin compositions obtained in Examples 1 to 7 and Comparative Example 1 were analyzed, and were found to be the same as those shown in Table 2.
[0106] [Table 2]
[0107] <Plate sample> (injection molding) The obtained thermoplastic resin composition pellets were put into an injection molding machine and molded into a 100 mm square plate with a thickness of 2 mm to prepare a plate sample for evaluation. The mold used had its surface (mold cavity inner surface) polished with a polishing grit of 8000. The molding conditions for the evaluation plate samples were set as follows. Molding temperature (cylinder temperature): 230℃ Mold temperature: 65℃ In addition, it is important to keep the mold temperature at a higher temperature during injection molding in order to improve the transferability of the mold surface polished with 8000 grit sandpaper. If the mold temperature is too high, the cooling time will be too long and it will become impractical. The mold temperature range that ensures these good results is 40°C to 100°C, more preferably 50°C to 90°C, and even more preferably 60°C to 85°C, and this time we selected 65°C.
[0108] <Dumbbell-shaped multipurpose test piece> (injection molding) The obtained pellets of the thermoplastic resin composition were put into an injection molding machine to mold a JIS type A1 dumbbell-shaped multipurpose test piece as a sample for evaluation under molding conditions conforming to JIS K6717.
[0109] As shown in Table 3, it was possible to produce thermoplastic resin compositions having both excellent transparency and toughness, and also exhibiting good resistance to yellowing during heat processing and processing stability, in Examples 1 to 6. In Example 7, the toughness was slightly inferior, although it was at a practically sufficient level. In Comparative Example 1, the methacrylic resin (A) having a ring structure in the main chain contained a large number of maleic anhydride monomer units, and therefore the yellowing resistance and processing stability during heat processing were not good.
[0110] [Table 3] [Industrial Applicability]
[0111] According to the thermoplastic resin composition of the present invention, a molded article having good transparency and excellent toughness and scratch resistance can be obtained, and therefore the composition has industrial applicability, for example, as roofing materials used in buildings, automobiles, trains, or buses, films for vinyl greenhouses, liquid crystal protective films, protective materials used in indoor and outdoor lighting, signs, and meters, vehicle interior and exterior components, vehicle lighting components, ship lighting components, battery protective covers, and the like.
Claims
1. A thermoplastic resin composition comprising 50 to 99 mass% of a methacrylic resin (A) having a ring structure in its main chain, the resin containing 80.0 to 99.9 mass% of methacrylic acid ester monomer units (a1), 0.1 to 20.0 mass% of vinyl monomer units (a2) copolymerizable with methacrylic acid ester monomers other than methacrylic acid esters, maleic acid, and maleic anhydride, and 0 to 4.0 mass% of maleic acid and / or maleic anhydride monomer units (a3), and 1 to 50 mass% of a thermoplastic polyurethane (B) containing a structural unit (b1) derived from a polyester polyol and a structural unit (b2) derived from an isocyanate having an alicyclic ring.
2. The thermoplastic resin composition according to claim 1, wherein the structural unit (b2) derived from an isocyanate having an alicyclic ring has one alicyclic ring.
3. The thermoplastic resin composition according to claim 1 or 2, wherein the weight average molecular weight of the methacrylic resin (A) having a ring structure in the main chain, as measured by gel permeation column chromatography (GPC), is 50,000 to 250,000.
4. 3. The thermoplastic resin composition according to claim 1, wherein the amount of terminal unsaturated double bonds in the methacrylic resin (A) having a ring structure in the main chain is 0.01 mol % or less.
5. The vinyl monomer unit (a2) copolymerizable with the methacrylic acid ester monomer other than the methacrylic acid ester, maleic acid, and maleic anhydride is an N-substituted maleimide monomer unit and / or a styrene-based monomer unit. The thermoplastic resin composition according to claim 1 or 2.
6. The thermoplastic resin composition according to claim 5, wherein the methacrylic resin (A) having a ring structure in the main chain contains 85 to 99.9% by mass of the methacrylic acid ester monomer unit (a1), 0.1 to 15% by mass of an N-substituted maleimide monomer unit, and 0 to 10% by mass of a styrene monomer unit.
7. 3. The thermoplastic resin composition according to claim 1, wherein a mass ratio of the structural unit derived from an isocyanate having one alicyclic ring relative to a total mass of the structural units derived from an isocyanate contained in the thermoplastic polyurethane (B) is 70 mass% or more.
8. The method for producing the thermoplastic resin composition according to claim 1 or 2, comprising a step of blending the methacrylic resin (A) having a ring structure in the main chain and the thermoplastic polyurethane (B) at a temperature in the range of 200 to 260°C.
9. A molded article comprising the thermoplastic resin composition according to claim 1 or 2.
10. An injection molded article comprising the thermoplastic resin composition according to claim 1 or 2.
11. A method for producing an injection molded article, comprising a step of molding the thermoplastic composition according to claim 1 or 2 at a cylinder temperature of 200 to 260°C.
Citation Information
Patent Citations
Acrylic resin film and injection molded item with it laminated thereto
JP2003183471A
Thermoplasticizable transparent mixtures of thermoplastic polyurethane and poly(meth)acrylate.
JP2015532345A
Transparent TPU (thermoplastic polyurethanes) / PMMA (polymethyl (METH)acrylate) blends with improved low-temperature impact resistance
WO2007057242A1